Eosinophil granule proteins expressed in ocular cicatricial pemphigoid. Issue 3 (1st March 1998) - Heiligenhaus, Arnd; Schaller, Jörg; Mauß, Sabine; Engelbrecht, Susan; Dutt, James E; Foster, C Stephen; Steuhl, Klaus-Peter
Abstract : BACKGROUND: Blister formation and tissue damage in bullous pemphigoid have been attributed to the release of eosinophil granule proteins—namely, to eosinophil derived cationic protein (ECP) and major basic protein (MBP). In the present investigation these eosinophil granule proteins were studied in the conjunctiva of patients with ocular cicatricial pemphigoid (OCP). METHODS: Conjunctival biopsy specimens obtained from patients with subacute (n=8) or chronic conjunctival disease (n=13) were analysed histologically and immunohistochemically using antibodies directed against EG1 (stored and secreted ECP), EG2 (secreted ECP), MBP, CD45 (common leucocyte antigen), CD3 (pan T cell marker), and HLA-DR (class II antigen). RESULTS: Subepithelial mononuclear cells, mast cells, and neutrophils were detected in all specimens. The number of mononuclear cells, neutrophils, CD45+ cells, CD3+ cells, and the HLA-DR expression were significantly higher in the subacute than in the chronic disease group. Some eosinophils were found in specimens from five of eight patients with subacute OCP, but in none of the patients with chronic disease. The eosinophil granule proteins (ECP and MBP) were found in the epithelium and substantia propria in patients with subacute conjunctivitis. CONCLUSIONS: Subepithelial cell infiltration in the conjunctiva greatly differs between subacute and chronic ocular cicatricial pemphigoid specimens. The findings suggest that eosinophil granule proteins may participate in tissue damage in acute phase of inflammation in OCP.